Calcitonin Gene-related Peptide (CGRP) Inhibitors in Episodic and Chronic Migraines: A Multiple Treatment Comparison (MTC) Meta-Analysis - Shita Meliani, Dewa Ayu Sri; Haq, Abiyyu Didar (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2025)
Migraine is a common neurological disorder affecting approximately 15% of adults worldwide, characterized by recurrent pulsating headaches. Conventional treatments often provide insufficient relief and may cause medication-overuse headaches. Calcitonin Gene-Related Peptide (CGRP) inhibitors have emerged as a novel preventive therapy by targeting the underlying migraine pathophysiology. This meta-analysis aimed to evaluate the efficacy and safety of CGRP inhibitors in reducing monthly migraine days (MMD) among patients with episodic and chronic migraine. A systematic search was conducted in ScienceDirect, PubMed, CENTRAL, and Wiley up to January 29, 2023, including randomized controlled trials with MMD as the primary outcome. Forty-two studies were analyzed qualitatively, and 32 studies were included in quantitative synthesis using random-effects models. Among 22,295 patients from studies published between 2013 and 2022, CGRP inhibitors significantly reduced MMD compared to placebo (Mean Difference -2.12; 95% CI -2.41 to -1.84; p=0.02), with galcanezumab showing the largest effect. Safety profiles were comparable to placebo, supporting their role in migraine prevention and guideline recommendations.